2009
DOI: 10.1111/j.1365-2966.2009.14388.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding versus feedback in NGC 4151 probed with Gemini NIFS - I. Excitation

Abstract: We have used the Gemini Near‐infrared Integral Field Spectrograph (NIFS) to map the emission‐line intensity distributions and ratios in the narrow‐line region (NLR) of the Seyfert galaxy NGC 4151 in the Z, J, H and K bands at a resolving power ≥5000, covering the inner ≈200 × 300 pc of the galaxy at a spatial resolution of ≈8 pc. We present intensity distributions in 14 emission lines, which show three distinct behaviours. (1) Most of the ionized gas intensity distributions are extended to ≈100 pc from the nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
242
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(294 citation statements)
references
References 77 publications
(168 reference statements)
48
242
1
3
Order By: Relevance
“…The mass of ionized gas derived for NGC 2110 is thus 3 orders of magnitude smaller than the estimated total mass of molecular gas, a result that is in agreement with those of previous studies (Ferruit et al 2004;Storchi-Bergmann et al 2009, 2010Riffel et al 2008.…”
Section: Mass Of the Molecular And Ionized Gassupporting
confidence: 91%
See 1 more Smart Citation
“…The mass of ionized gas derived for NGC 2110 is thus 3 orders of magnitude smaller than the estimated total mass of molecular gas, a result that is in agreement with those of previous studies (Ferruit et al 2004;Storchi-Bergmann et al 2009, 2010Riffel et al 2008.…”
Section: Mass Of the Molecular And Ionized Gassupporting
confidence: 91%
“…The H 2 emission is dominated by rotational motion and shows lower velocity dispersion values than the ionized gas. From the gas excitation and kinematics, we have found that the emitting H 2 gas (hot molecular gas, as it originates in gas at ≈ 2000 K, Storchi-Bergmann et al (2009)) is located in the plane of the galaxy, presenting a velocity field dominated by rotation. In some cases, in the inner ≈ 30 pc of the galaxy, compact molecular disks (Hicks et al 2013;Mazzalay et al 2014;Riffel & Storchi-Bergmann 2011a;Schönell et al 2013) and gas inflows along nuclear spirals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The only exception is the H 2 emission in NGC 4151 and NGC 4388, which shows a small depression towards the nucleus. The former is consistent with a central hole in the H 2 (1−0)s(1) distribution observed by Fernandez et al (1999) and Storchi-Bergmann et al (2009). NGC 3185 shows a secondary peak at the location of the circumnuclear star forming ring (Comerón et al 2010).…”
Section: Nuclear Vs Off-nuclear Aperturessupporting
confidence: 84%
“…However, similar drops towards the nucleus have also been observed, with high spatial resolution integral field spectrographs, in [FeII]1.26 μm/Paβ ratio maps (e.g. Storchi-Bergmann et al 2009;Riffel et al 2010Riffel et al , 2011. The ratio [FeII]1.26 μm/Paβ is nearly insensitive to reddening, due to the small wavelength separation between the two lines.…”
Section: Nuclear Vs Off-nuclear Aperturessupporting
confidence: 66%
“…The AGNIFS group obtained masses in a range of 66 M ≤ M H 2 ≤ 3300 M and 0.1 × 10 6 M ≤ M H  ≤ 17 × 10 6 M in the nuclear regions of nearby galaxies (Riffel et al 2008(Riffel et al , 2010Storchi-Bergmann et al 2009;Schönell et al 2014). We conclude that the LLQSO HE 1029-1831 has a large reservoir of cold molecular gas that is needed and apparently used for both star formation and black hole fueling.…”
Section: Mass Of Ionized and Molecular Gasmentioning
confidence: 75%